(untitled) - Khounsysounthone, Thongdam (Can Tho, 2020)
The objectives of this study were to investigate and assess the water quality parameters and zooplankton composition to serve as database for development of a zooplankton based biomonitoring system for water quality assessment in the Hau River. The study was implemented four times a year (March, June, September and December, 2019) at An Giang (upstream), Can Tho (middle stream) and Soc Trang (downstream). Sampling was conducted at 29 sites (including 14 locations in the main river and 15 sites in its tributaries). The results showed that a total of 167 zooplankton species were recorded. Among them, Rotifera was the most abundant group with 64 species (accounting for 48%), followed by Protozoa with 48 species (29%), Copepoda with 27 species (16%), and other taxa range of 10-18 species (6-11%). Species composition and density of zooplankton in its tributaries were higher than that in the main river.
Keywords: Động vật phù du,Zooplankton